Transcranial direct current stimulation with multiple oral re-reading therapy for pure alexia without agraphia: a case report - Mohamad, Nur Afiqah; Che Adinana, Siti Nadia; Yusof Khan, Abdul Hanif Khan; Nik Abdul Ghani, Nik Nor Haramaini; Al-Khafiz Kamis, Mohammad Fandi; Wan Sulaiman, Wan Aliaa; Salim, Mazatulfazura Sf; Basri, Hamidon (Taylor and Francis Group, 2021)
Pure alexia without agraphia is characterized by impaired reading due to damage to the occipitotemporal cortex with preserved writing skills. In this case report, we investigate the effect of multiple oral re-reading (MOR) therapy adjunct with transcranial direct current stimulation (tDCS) in improving reading recovery of a 64-year-old patient with pure alexia without agraphia following a stroke. His MRI revealed an area of infarct with microhemorrhages at the left occipitotemporal region. The patient was blinded to each therapy and underwent seven consecutive sessions of sham tDCS followed by seven consecutive sessions of real tDCS, coupled with 1-hour MOR therapy during each session. Western Aphasia Battery (WAB) was performed at baseline, before sham and real-tDCS, and 6 weeks after completing tDCS therapy. The patient showed improvement using both sham and real-tDCS with better reading comprehension, average reading time, and word per minute after real-tDCS. This study suggests that MOR, coupled with tDCS therapy may accelerate the reading recovery in patients with pure alexia.